Statics Analysis and Structure Parameter Design of the Lower Limb Rehabilitation Robot - Cui Bingyan; Chen Liwen; Wang Zhijun; Li Zhanxian (Jixie chuandong)
The lower limb rehabilitation robot is an automated functional rehabilitation equipment,with a scientific and reasonable rehabilitation conditions,the patients can make their lower extremity motor function get good recovery. In order to improve the rehabilitation training work space of the lower limb rehabilitation robot,increases the bearing capacity,the statics analysis of rehabilitation robot is very important. A kind of lower limbs rehabilitative robot with 3- UPS parallel mechanism as the mechanism prototype is puts forward,the statics equations of the lower limb rehabilitation robot driving force and output force are established based on the virtual work principle,the static performance evaluation index is defined and the evaluation index distribution map is drawn. The relationship between the structure parameters and the statics performance evaluation indexes is analyzed,the influence of structure parameters on the statics performance is obtained. And the lower limb rehabilitation robot is designed based on the structure parameters. The analysis results lay a foundation for further analysis and research of the lower limbs rehabilitative robot.